Tobacco use and looked-after children: developing a complex intervention to address smoking in residential care - Huddlestone, Lisa (2019)
Levels of tobacco smoking among looked-after children (LAC) substantially exceed those reported among the general youth population. Research highlights that smoking is common among LAC, further increasing the health and social inequality experienced by this vulnerable group. However, there is limited research evidence about smoking and the factors that influence tobacco use in residential units, and if opportunities exist to address tobacco use in residential care. The overall purpose of this thesis was to develop a theory- and evidence-based intervention to address tobacco use in residential units for LAC.